Randomized controlled trial on the effect of an online decision aid for young female cancer patients regarding fertility preservation - Ehrbar, Verena; Urech, Corinne; Germeyer, Ariane (Human reproduction, 2019)
AbstractStudy question. Does the use of an online decision aid (DA) about fertility preservation (FP), in addition to standard counselling by a specialist in r
Gesehen am 10.12.2019